HUBUNGAN ANTARA KEPEMIMPINAN VISIONER DAN EFIKASI DIRI DENGAN PRODUKTIVITAS KERJA GURU - Yun Soung Suk; Sumardi Sumardi; Karantiano Sadasa Putra (JURNAL MANAJEMEN PENDIDIKAN, 2018)
The purpose of this study is to analyse the correlation of visionary leadership and self efficacy to teachers work productivity. This study is conducted in primary public school in District of Tamansari. The study population is 168 teachers and the number of sample is 118 teachers decided by proportional random sampling. Data were collected by questionnaire. The data analysis technique applied correlation regression partial and multiple. The result shows that there is positive correlation between vissionary leadership and teachers work productivity (the correlation coefficient ry1 = 0,530 and the detemination coefficient r2 y1=0,281), there is positive correlation between self efficacy and teachers work productivity (the correlation coefficient ry2 =0,472 and the determination coefficient r2 y2=0,222), and there is positive correlation of visionary leadership and self efficacy to teachers work productivity (the correlation coefficient ry12 = 0,562 and the determination coefficient R2 y.12= 0,316). Based on the result, it can be concluded that the teachers work productivity could be enhanced through visionary leadership and self efficacy either partially or concurrently.Keyword: teachers work productivity, visionary leadership, self efficacy